Comparative study between dexmedetomidine and dexamethasone as an adjuvant to levobupivacaine for supraclavicular brachial plexus block in patients undergoing upper limb surgeries - Suman Sarkar; Debarati Goswami; Sujan Sarkar; Sandesh Rathod (Asian Journal of Medical Sciences, 2023)
Background: Brachial plexus block (BPB) is widely used nowadays in patients undergoing upper limb surgery. Levobupivacaine is one of the best local anesthetics in the current scenario in this field. Both dexmedetomidine (DM) and dexamethasone (DX) are commonly used local anesthetic adjuvants in BPB to enhance blocking effects. In anesthesiology, there is always a search for a better alternative.